2023
DOI: 10.3389/fpsyg.2022.1090181
|View full text |Cite
|
Sign up to set email alerts
|

Multiple examinations indicated associations between abnormal regional homogeneity and cognitive dysfunction in major depressive disorder

Abstract: BackgroundThis study aimed to investigate the relationships between regional neural activity and multiple related indicators in patients with major depressive disorder (MDD).MethodsForty-two patients and 42 healthy controls (HCs) were enrolled. Pearson/Spearman correlation analyses were applied to examine the associations between abnormal regional homogeneity (ReHo) and different indicators in the patients.ResultsCompared with HCs, patients with MDD had increased ReHo in the left inferior temporal gyrus (ITG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 111 publications
(109 reference statements)
1
0
0
Order By: Relevance
“…The neural functioning of the left putamen has also been implicated in the risk of bipolar disorder onset, suggesting a potential marker of vulnerability [ 99 ], as well as suicidality in bipolar II disorder [ 100 ]. Our results are consistent with decreased putamen regional homogeneity reported in adult patients with MDD [ 101 , 102 ], and with a recent SPECT study that showed negative correlation between levels of depression, anxiety, anhedonia and psychomotor retardation and DAT availability in the left putamen [ 103 ]. The same study showed lower left putamen DAT availability in seriously depressed patients and in patients with significant psychomotor retardation [ 103 ].…”
Section: Discussionsupporting
confidence: 93%
“…The neural functioning of the left putamen has also been implicated in the risk of bipolar disorder onset, suggesting a potential marker of vulnerability [ 99 ], as well as suicidality in bipolar II disorder [ 100 ]. Our results are consistent with decreased putamen regional homogeneity reported in adult patients with MDD [ 101 , 102 ], and with a recent SPECT study that showed negative correlation between levels of depression, anxiety, anhedonia and psychomotor retardation and DAT availability in the left putamen [ 103 ]. The same study showed lower left putamen DAT availability in seriously depressed patients and in patients with significant psychomotor retardation [ 103 ].…”
Section: Discussionsupporting
confidence: 93%